Kajian Struktur pada Wacana Pemberitaan Perubahan Iklim dalam Harian Le Monde dan Le Figaro: Kajian Analisis Wacana Kritis - Prameswari, Adelia Ika; Sunendar, Dadang; Widawati, Rika (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2025)
This study aims to describe the textual dimensions in news discourse on climate change in the online media Le Monde and Le Figaro, using the Critical Discourse Analysis model developed by Teun A. Van Dijk. This study uses a descriptive qualitative approach with documentation techniques on four online news articles about climate change published in Le Monde and Le Figaro in 2024, selected based on the theme of the global climate crisis and its visibility on the main page. The analysis was conducted by identifying global themes, news structure schemes, and semantic, syntactic, stylistic, and rhetorical devices based on Van Dijk's text dimension model. The results show that both media outlets highlight the global climate crisis as a macro theme, but organize information differently and utilize contrasting micro devices. Le Monde more frequently uses evaluative lexicon and references to global political actors to frame climate change as a failure of diplomacy, while Le Figaro emphasizes scientific legitimacy through expert quotes and quantitative data, creating an impression of technocratic urgency. These findings clarify how media ideological orientation influences climate crisis meaning-making strategies and demonstrate the usefulness of Van Dijk's text dimension framework for revealing differences in climate framing in French-language mainstream media.